Mid-Late Holocene Sub-Millennial Scale Inverse Trends of South Asian Summer and Winter Monsoons in Sri Lanka - Gayantha, Kasun; Roberts, Patrick; Routh, Joyanto; Wedage, Oshan; Ott, Florian; Frenzel, Peter; Chandrajith, Rohana; Gleixner, Gerd (Frontiers in Earth Science, 2021)
The South Asian Monsoon (SAM) brings precipitation crucial for agriculture across the densely populated region of South Asia. Identifying the key long-term drivers of the SAM is essential to improve the predictability of future monsoonal trends in the context of current global climate scenarios and increasingly frequent drought and flooding events in this part of the world. Here, we reconstruct ~6000 years of climatic and environmental history of the South Asian summer monsoon-fed Bolgoda South Lake and the Horton Plains, and the winter monsoon-fed Panama lagoon, in Sri Lanka to better understand monsoonal operation over this island and its connection to broader climate systems. Multiple proxies (diagnostic biomarkers, hydrogen and carbon isotopes of individual n-alkane, grain size, and Zr/Rb elemental ratio) indicate a sub-millennial scale decreasing trend of summer monsoon rainfall in the wet zone of Sri Lanka alongside an increasing trend of winter monsoon rainfall in the dry zone. We also observed multi-centennial scale arid events in the Bolgoda South Lake and Horton Plains records at ~3,500 and ~1,000 cal years BP. Inverse monsoonal behavior during the mid- and late Holocene seems to be led by the southward migration of the mean latitudinal position of ITCZ, induced by varying solar energy distribution between the Northern and Southern hemispheres due to Earth’s processional cycle. Our observations are broadly supported by existing paleoclimatic records from the Indian sub-continent, but abrupt arid phases are asynchronous in the regional records. In addition, these short-term arid conditions do not show systematic correlations with the different modes of climate variables known to have teleconnections with the Indian Ocean monsoon.